Urinary HER2, TWEAK and VCAM-1 levels are associated with new-onset proteinuria in paediatric lupus nephritis - Michelle A Petri; Emily von Scheven; Marisa S Klein-Gitelman; Patricia Costa-Reis; Kelly Maurer; Kathleen E Sullivan; Daniella Levy Erez; Xue Zhao; Walter Faig; Jon Burnham; Kathleen O'Neil (Lupus Science and Medicine, 2022)
Objective Lupus nephritis is a key driver of morbidity and mortality in SLE. Detecting active nephritis on a background of pre-existing renal damage is difficult, leading to potential undertreatment and accumulating injury. An unmet need is a biomarker that distinguishes active lupus nephritis, particularly important in paediatrics where minimising invasive procedures is desirable.Methods This was a multicentre, prospective study of 113 paediatric patients with biopsy-proven lupus nephritis. Clinical data and urine were obtained every 3–4 months and patients averaged 2 years on study with seven time points. Urine was analysed for human epidermal growth factor receptor 2 (HER2), tumour necrosis factor-like weak inducer of apoptosis and vascular cell adhesion molecule-1 (VCAM-1) by ELISA. We defined active disease as either a rise in serum creatinine ≥0.3 mg/dL from baseline or a rise in renal Systemic Lupus Erythematosus Disease Activity Index score from the previous visit. These markers were also studied in patients with acute kidney injury, juvenile idiopathic arthritis (JIA), amplified pain syndrome and healthy controls.Results The rate of active disease was 56% over an average of 2 years of follow-up. HER2 and VCAM-1 were significantly elevated at time points with active disease defined by increased serum creatinine compared with time points with inactive disease or patients who never flared. All three biomarkers were associated with new-onset proteinuria and VCAM-1 was elevated at time points preceding new-onset proteinuria. These biomarkers were not increased in acute kidney injury or JIA.Conclusion All three biomarkers were associated with new onset proteinuria and increased VCAM-1 may predict impending proteinuria. These biomarkers provide potential non-invasive measures for monitoring that may be more sensitive to impending flare than conventional measures.